2022
DOI: 10.1101/2022.05.23.493056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unbiased proteomic and forward genetic screens reveal that mechanosensitive ion channel MSL10 functions at ER-plasma membrane contact sites in Arabidopsis thaliana

Abstract: Mechanosensitive (MS) ion channels are an evolutionarily conserved way for cells to sense mechanical forces and transduce them into ionic signals. The channel properties of Arabidopsis thaliana MscS-Like (MSL)10 have been well studied, but how MSL10 signals remains largely unknown. To uncover signaling partners of MSL10, we employed both a proteomic screen and a forward genetic screen; both unexpectedly implicated ER-plasma membrane contact sites (EPCSs) in MSL10 function. The proteomic screen revealed that MS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…As the EPCS occupies a large portion of the cell surface (larger than 10%), its regulation of ion channel activity is essential in neuronal physiology (Johnson et al ., 2018). Recent proteomic and forward genetic screens revealed that a PM‐localised mechanosensitive (MS) ion channel, MSL10, interacts with VAP27 in Arabidopsis (Codjoe et al ., 2022), suggesting a similar mechanism may exist in plants. It is highly possible that in certain cell types, for example guard cells, additional regulation of ion channels is important.…”
Section: The Biological Relevance Of Plant Er–pm Contact Sitesmentioning
confidence: 93%
See 1 more Smart Citation
“…As the EPCS occupies a large portion of the cell surface (larger than 10%), its regulation of ion channel activity is essential in neuronal physiology (Johnson et al ., 2018). Recent proteomic and forward genetic screens revealed that a PM‐localised mechanosensitive (MS) ion channel, MSL10, interacts with VAP27 in Arabidopsis (Codjoe et al ., 2022), suggesting a similar mechanism may exist in plants. It is highly possible that in certain cell types, for example guard cells, additional regulation of ion channels is important.…”
Section: The Biological Relevance Of Plant Er–pm Contact Sitesmentioning
confidence: 93%
“…Recent proteomic and forward genetic screens revealed that a PMlocalised mechanosensitive (MS) ion channel, MSL10, interacts with VAP27 in Arabidopsis (Codjoe et al, 2022), suggesting a similar mechanism may exist in plants. It is highly possible that in certain cell types, for example guard cells, additional regulation of ion channels is important.…”
Section: Reviewmentioning
confidence: 99%
“…This response is dependent on the phosphorylation of MSL10 N-terminus (Veley et al 2014;. In a recent preprint, MSL10 was found to localize and function at ER-plasma membrane contact sites (EPCSs) (Codjoe et al 2022). In plants, EPCSs regulate lipid homeostasis between compartment and cell integrity (Schapire et al 2008;Ruiz-Lopez et al 2021).…”
Section: Mechanosensitive Channels (Msl Osca1 Piezo …)mentioning
confidence: 99%